2018 Twenty Fourth National Conference on Communications (NCC) 2018
DOI: 10.1109/ncc.2018.8599981
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Underlaid Multi-antenna D2D on Cellular Downlink in Massive MIMO Systems

Abstract: In this paper, we consider a massive multiple-input multiple-output (MIMO) downlink system underlaid with a network of multi-antenna D2D user equipments (UEs). Each D2D transmitter (Tx) uses all its antennas to beamform information towards its desired D2D receiver, which uses only a single antenna for reception. While beamforming at the D2D Tx reduces D2D interference to the neighbouring cellular UEs (CUEs), the cellularto-D2D interference is also negligible due to highly directional beamforming at the massive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The authors in [16,[23][24][25]35] have studied the achievable data rate, and energy efficiency tradeoff for D2D enabled downlink massive MIMO system employing a stochastic geometry-based analytical framework. However, these works didn't consider any resource allocation scheme for interference management and showed that the density of D2D users limits the benefits of the coexistence of D2D and massive MIMO.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors in [16,[23][24][25]35] have studied the achievable data rate, and energy efficiency tradeoff for D2D enabled downlink massive MIMO system employing a stochastic geometry-based analytical framework. However, these works didn't consider any resource allocation scheme for interference management and showed that the density of D2D users limits the benefits of the coexistence of D2D and massive MIMO.…”
Section: Related Workmentioning
confidence: 99%
“…The work in [24] considered a scenario when a massive MIMO system underlaid with multi-antenna D2D users. They employed beamforming techniques at a D2D transmitter and massive MIMO antenna BS to reduce D2D-to-cellular and cellular-to-D2D interference.…”
Section: Related Workmentioning
confidence: 99%
“…In the work of Liu et al, 11 considering in such systems, the pilot overhand becomes large with the number of cellular and D2D UEs, authors have proposed pilot reuse for D2D underlay massive MIMO systems to reduce the pilot overhand and to increase the system throughput. The impact of channel state information on the D2D underlay massive MIMO systems has been further evaluated in the work of Lin et al 12 While previous works 12,13 focused on the uplink of massive MIMO system, with D2D underlay communication mode, the work of Agarwal et al 14 investigated the downlink, where the D2D UEs are equipped with multiple antennas and maximum ratio transmission is used to transmit signals. Beamforming at D2D transmitters reduces the D2D interference to neighboring cellular UEs.…”
Section: Funding Informationmentioning
confidence: 99%
“…It is easy to see that the works [10][11][12][13][14] mainly contributed to interference management and evaluating the effect of interference on system spectral efficiency without the consideration of energy efficiency. That is to say, in previous works, [10][11][12][13][14] the mutual interference between D2D and cellular users (CUs) has been purely considered as an obstacle. However, it is well known that in practical systems, the D2D transmitters are usually power limited or even battery free.…”
Section: Funding Informationmentioning
confidence: 99%